EFFECTIVENESS OF INFORMATION SERVICES TO IMPROVE STUDENTS' LEARNING INDEPENDENCE - Siregar, Rafiqah Umry; Darmayanti, Nefi (Universitas Islam Negeri Syekh Ali Hasan Ahmad Addary Padangsidimpuan, 2024)
Education plays a major role in supporting national development which is an effort to improve the quality of life, personal and community quality that lasts a lifetime. Education is an effort to shape individuals to be better and more useful for the future. This research aims to determine the effectiveness of information services to increase student learning independence. Utilization of information services so that students gain broader knowledge is expected to increase student learning independence. The method in this research is the SLR Prisma (Systematic Literature Review) method, this method is used to develop a framework for writing scientific papers. The results of this research indicate that information services can increase student learning independence. In bridging the problem of students' independent learning, guidance from teachers and parents is needed. Guidance is assistance provided to students in self-development and good study habits to master certain knowledge. This research can be used as a solution for teachers, especially those who have a relationship with students.